Information and security components of the Russian foreign policy - Zaitseva, Mariia (Information & Media, 2015)
The aim of the paper is to examine the Russian Federation’s doctrines in the sphere of information security. Such analysis allowed to lay down the information and security strategy of the state in the international arena and to study the specifics of the Russian model of information security. It was also determined that in order to counteract information threats, the Russian political administration continues an active development of cooperation with such actors as SCO and BRICS which de jure keep the neutral position concerning the Russian–Ukrainian relations, but de facto continue to expand economic cooperation with the RF. In the article, reviewed are the instruments of Russia’s modern information and propaganda operations, which were used in Chechnya and Georgia, and the specifics of propaganda operations against Ukraine are analysed.